Severe cachexia and prolonged stay in the intensive care unit following ingestion of caigua - (:unkn) unknown (My University, 2012)
We aimed to present a case with severe cachexia in the early period after ingestion of caigua (cyclanthera pedata) which is a slender tropical vine indigenous to South America. A 15-year-old male patient was referred to our intensive care unit with acute nausea and vomiting, muscle weakness, metabolic acidosis, respiratory failure, and loss of consciousness. His past medical history was unremarkable. He had eaten caigua shortly before onset of symptoms. He had rapidly progressive cachexia and lost more than 20 percent of his weight over 1 month. "Acute disseminated encephalomyelitis (ADEM) syndrome" had been considered as one possible differential diagnosis, but there was no diagnostic feature shown on the magnetic resonance imaging (MRI). Caigua is being used especially to lose weight widely around the world and caigua poisoning should be kept in mind in patients having rapid onset of unexplained cachexia.
Keywords: Acute disseminated encephalomyelitis; Cachexia; Caigua; Ingestion; Intensive care